Cuban chamber music at the beginning of the 21.st century: Yalil Guerra and Old Habana (Islas, 2022)
ABSTRACTIntroduction: By studying the musical framework of Cuban composers who are located in a foreign environment, we approach a process of connections that includes different points of view and that, in turn, are discursively intertwined in a scenario that builds cultural codes that reinforce the identity. Within this framework, the work provides special analytical attention to the production of Chamber music by Yalil Guerra Soto (1973).Methods: In this research, the analysis proposal based on the enactive criterion is developed, that is, multivalent and interacting relationships that are unleashed in recipient-creator individuality from specific topics evoked, considering that every analyst is in turn a perceiving subject. -Creative of the work he faces. For traditional historiography, Chamber music is linked to a number of members of an instrumental/vocal format of genres established at the time of classicism, which are performed in a relatively small and intimate space.Results: We focus on an analytical approach to his musical proposal Old Havana by the composer and guitarist Yalil Guerra for its interconnections between academic and popular music. The sound context exposes a traditional string quartet. The timbre image is conventional, but in turn contains a range of profiles that support the discourse and combine effects of semantic interconnection, giving it a unique aesthetic vision. The alternation of compass according to the discursive requirement is notable, acquiring diversity in the development sections.Conclusions: the cameral concept extends its scope to the genres considered folkloric or popular, interweaving a unifying thought that describes music as a whole. We analyse and corroborate in the work of Yalil Guerra, the resignification, of the sound world of traditional Cuban popular music in an academic context.
Keywords: musical composition; identity; cultural codes; Chamber music